2020
DOI: 10.1016/j.tranon.2019.09.012
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of High-mobility Group Box Mutation of T-cell Factor 4 on Its Genomic Binding Pattern in Non–small Cell Lung Cancer

Abstract: T-cell factor 4 (TCF-4) is determined to play a crucial role in Wnt/β-catenin signaling pathway activation. The mutations and alternative splice isoforms of TCF-4 can cause cancers and other diseases. The high-mobility group (HMG) box domain of TCF-4 contributes to interacting with DNA motif for transcriptional regulation. However, the impact of the mutations within HMG box of TCF-4 on the genomic binding pattern is poorly investigated. Herein, we generated non–small cell lung cancer (NSCLC) cell line A549 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The HMG box is the domain responsible for the binding to and recognition of Wnt response elements (WREs), so, changes in the coding sequences of the HMG box could alter this recognition as well as binding affinities. Recently, one study identified several mutations in the TCF7L2 HMG box that are associated with lung cancer (Su et al., 2020 ). One of these mutations is precisely the change from valine (V) to isoleucine (I) at HMG‐box position 22 that we have found to be a specific change conserved across the TCF7 subfamily (Figure 4b ).…”
Section: Discussionmentioning
confidence: 99%
“…The HMG box is the domain responsible for the binding to and recognition of Wnt response elements (WREs), so, changes in the coding sequences of the HMG box could alter this recognition as well as binding affinities. Recently, one study identified several mutations in the TCF7L2 HMG box that are associated with lung cancer (Su et al., 2020 ). One of these mutations is precisely the change from valine (V) to isoleucine (I) at HMG‐box position 22 that we have found to be a specific change conserved across the TCF7 subfamily (Figure 4b ).…”
Section: Discussionmentioning
confidence: 99%